Сonstruction and analysis of the pole-changing windings for the pole pairs ratio 5/6 by method discretely specified spatial function - Bobojanov М.K., Rismukhamedov D.A., Tuychiev F.N., Shamsutdinov H.F. and Magdiev H.G. (International Journal of Advanced Science and Technology, 2020)
In the paper the method for receiving and the detailed analysis of electromagnetic properties pole-changing windings for the pole pairs ratio 5/6 in the 54 stator slots is presented by method discretely specified spatial functions. The new winding is intended for applying in mechanisms with the fan by type of loading with a view of power- and savings resource. The analysis of the electromagnetic properties of the obtained winding is carried out.  As a result of the study, there were procured the stator windings at 10 and 12 poles, which enabled to change the spin speed of the motor in the fan drives without breaking the drive power circuit by the scheme ΥΥΥ/ΥΥΥ with additional branches.